Chronic performance of Riata 1580 and Endotak 0158 ICD leads: A single center 10‐year experience. Issue 7 (17th June 2020) - Cobb, Vanessa; Ezzat, Vivienne; Higgins, Fiona; Lambiase, Pier; Lowe, Martin; Segal, Oliver; Chow, Anthony
Abstract: Background: The long‐term performance of the Riata family of leads has recently come under increasing scrutiny. We aimed to determine the long‐term performance of the Riata 1580 leads compared with Endotak 0158 leads. Methods: All patients with Riata 1580 or Endotak 0158 leads implanted from 2003 to 2008 at the Heart Hospital, UCLH were analyzed. Significant electrical changes were as follows: threshold increase >1 V at a set pulse width between pacing checks, persistent R wave fall to <2 mV or reduction in R wave >50%, noise, pacing impedance change to <300 Ω or >1500 Ω, high voltage (HV) change to <20 Ω or >200 Ω, HV change ± 15 Ω, pacing impedance change >400 Ω over 12 months. Results: 333 Riata and 356 Endotak leads were implanted. Median follow‐up time + interquartile range were calculated, after exclusion of censored events including loss to follow‐up: Riata 3652 + 655 days, Endotak 3730 + 810 days. A total of 51 (15.9%) Riata leads and 21 (6.3%) Endotak leads were affected. A greater risk of failure was found for the Riata lead compared with the Endotak lead ( P = .0001). An additional time‐dependent effect was found, with the Riata lead 1.9 times more likely to fail in the first 6 years following lead implantation and 5.3 times more likely to fail after 6 years. Conclusions: Riata leads have a higher risk of failure compared to Endotak leads over time. The importance of careful ongoing performance surveillance late in the leads' lifetime is reflected in this 10‐year follow‐up study.